Grace - Evans, Richard Paul. (New York : Simon & Schuster, 2008)
An old man reminisces about his first love, a young runaway who taught him more about life than anyone had before or since.
Keywords: Reminiscing in old age -- Fiction; First loves -- Fiction; Runaway teenagers -- Fiction; Christmas stories